2010
DOI: 10.4314/bajopas.v1i1.57512
|View full text |Cite
|
Sign up to set email alerts
|

Activity of <i>Bryophyllum pinnatum</i> S. Kurz extracts on respiratory tract pathogenic bacteria

Abstract: Ethanol extract of Bryophyllum pinnatum (commonly known as 'Shuka halinka' or 'Karan masallachi' in Hausa) (BP1) was partitioned into n-hexane, chloroform, ethyl acetate and aqueous methanol soluble fractions and labeled BP1-01, BP1-02, BP1-03 and BP1-04 respectively. These fractions were subjected to antibacterial testing against respiratory tract pathogenic bacteria. The n-hexane soluble fraction showed activity against the selected microorganism with highest on Staphylococcus aureus (12mm), Klebsiella pneum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 12 publications
1
11
0
Order By: Relevance
“…The ability of extracts from FOPF inhibits bacterial growth in the moderate to strong, because the diameter of the inhibition zone ranges from 6.67-12.83 mm. In accordance with the statement of Davis and Stout [29] and Mudi and Ibrahim [30] if the diameter of the inhibition zone is more than 6 mm, the extract has antimicrobial activity with a moderate to strong category. Table 5 shows the diameter of the inhibitory zone in Gram-negative bacteria (E. coli) generally greater than the Gram-positive bacteria (S. aureus).…”
Section: Antimicrobial Activity Test Of Extracts From Fopf (In Vitro)supporting
confidence: 77%
“…The ability of extracts from FOPF inhibits bacterial growth in the moderate to strong, because the diameter of the inhibition zone ranges from 6.67-12.83 mm. In accordance with the statement of Davis and Stout [29] and Mudi and Ibrahim [30] if the diameter of the inhibition zone is more than 6 mm, the extract has antimicrobial activity with a moderate to strong category. Table 5 shows the diameter of the inhibitory zone in Gram-negative bacteria (E. coli) generally greater than the Gram-positive bacteria (S. aureus).…”
Section: Antimicrobial Activity Test Of Extracts From Fopf (In Vitro)supporting
confidence: 77%
“…Tannins are also reported to have various physiological effects like anti-irritant, antisecretolytic, antiphlogistic, antimicrobial and antiparasitic effects. Phytotherapeutically, tannin containing plants are used to treat non-specific diarrhoea, inflammations of mouth and throat and slightly injured skins [7]. This study revealed moderate in vitro antibacterial activity against test bacterial isolates at higher concentrations while at lower concentrations ranging from 25.0 to 6.25mg/ml, no inhibition zone was observed.…”
Section: Discussionmentioning
confidence: 72%
“…The plant has been found to possess antibacterial activity against several bacterial pathogens including Staphylococcus aureus, Escherichia coli and Pseudomonas aeruginosa. Different solvents such as aqueous, ethanol, methanol and n-hexane have been used for extraction and the respective extracts have shown varying degree of antibacterial actions against selected pathogens [7]. Irrespective of the researches so far, adequate information on the antibacterial activity of the plant extract is very important.…”
Section: Introductionmentioning
confidence: 99%
“…The GP extract tested in our study showed a three-fold lower MIC (2.5 mg/mL) on S. aureus than the BP methanol extract (6.25 mg/mL), suggesting that methanol is a better solvent for extraction of constituents with antibacterial activity than water. In addition, the GP extract exerted a four-to six-fold stronger inhibitory potential on S. aureus than the BP ethanol extract (MIC ¼ 10 mg/mL) obtained from B. pinnatum Kurz [38]. Considering the estimated maximal dose without adverse effects (1 mg/kg bw) in rats for aqueous GP extracts [19], our result (MIC ¼ 2.5 mg/mL) suggests that systematic application of the GP extract for treatment of Grampositive bacterial infections could be problematic.…”
Section: Antibacterial Activity Of Total Gp Extractmentioning
confidence: 92%